Understanding children’s emotions: differences in mothers with a history of childhood maltreatment - Milan, Stephanie (Child maltreatment, 2022)
Experiencing maltreatment in childhood can have a lasting impact on how individuals identify and understand emotions in others. Research in this area has not examined parents’ understanding of children’s emotions, although emotion processing deficits may be one mechanism linking childhood maltreatment to subsequent parenting problems. In a matched case-control design, we test whether mothers with (n = 50) and without (n = 96) childhood maltreatment differ in their understanding of children’s emotions on self-report measures and computer-based tasks. Compared to the control group, mothers who experienced maltreatment labeled more children with sad or angry emotions when given limited facial information and made different interpersonal inferences about children they labeled angry. They also reported more subjective difficulty interpreting emotions in unknown children and their own child. Results provide further evidence of emotion processing biases associated with childhood maltreatment. Interventions aimed at improving parental emotion understanding and mentalization may be particularly useful for mothers with a history of childhood maltreatment.